Analysis of Arabic Textbook for Grade VII Merdeka Curriculum Based on Textbook Praxeological Analysis - Shofwan Sholahudin; Agil Husein Al Munawar; Maman Abdurrahman (Didaktika: Jurnal Kependidikan, 2025)
This study aims to analyze the textbook Semangat Mendalami Bahasa Arab for Grade VII MTs published by Erlangga using a praxeological approach, which evaluates four main components: type of task, technique, technology, and theory. The method employed is qualitative descriptive with a content analysis design focusing on tarkib (syntax) material. The results show that the textbook incorporates 13 types of tasks using an inductive technique, where students are encouraged to analyze sentence or phrase examples to understand grammatical patterns. Visual aids such as tables are effectively used to simplify the relationships between constituents and support practical applications like self-introduction. However, several shortcomings are identified, such as the inconsistency in the sequence of materials, which, while not causing significant ontogenetic conceptual obstacle, and the lack of explanation for technical terms like nakirah and ma‘rifah, may lead to epistemological obstacle. In terms of theory, the textbook supports broader knowledge construction by fostering practical communication skills through structured tasks and contextual applications. Thus, while the textbook has the potential to be an effective learning resource, improvements in material sequencing and theoretical explanations are needed to better support comprehensive Arabic language learning.